2015
DOI: 10.1111/crj.12308
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with pulmonary thromboembolism: neutrophil to lymphocyte ratio and platelet to lymphocyte ratio

Abstract: The results of our study suggest that using non-invasive method such as ultrasonography combined with NLR and PLR in endothelial dysfunction diagnosis in PTE patients are both effective and inexpensive. We believe in PTE patients endothelial dysfunction may play a role in the development of probable cardiovascular events in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
0
30
2
Order By: Relevance
“…Moreover, ED independently predicted endothelial dysfunction among middle‐aged men presenting for wellness screening (Peyton et al ., ). An association between NLR and endothelial dysfunction was previously reported in men with pulmonary thromboembolism (Kurtipek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, ED independently predicted endothelial dysfunction among middle‐aged men presenting for wellness screening (Peyton et al ., ). An association between NLR and endothelial dysfunction was previously reported in men with pulmonary thromboembolism (Kurtipek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Altintas et al [ 33 ] found that a higher PLR is significantly associated with the presence of silent brain infarcts (SBIs) in patients with paroxysmal atrial fibrillation (PAF) ( P = 0.001); increased PLR might be a factor that induces inflammatory processes on SBIs in patients with PAF even with low CHA2DS2–VASc scores. Kurtipek et al [ 34 ] showed that in pulmonary thromboembolism (PTE) patients, using noninvasive ultrasonography combined with higher PLR in endothelial dysfunction diagnosis is effective. The study of Zuo et al [ 35 ] proved that the PLR was a predictive marker of thrombogenesis in nonvalvular atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] Recently, the pathophysiology of severe PE has been extended beyond simple RV obstruction. Several studies highlighted the role of inflammation [ 15 ] and endothelial dysfunction [ 16 ] in the alteration of organ perfusion at the microcirculation level in the context of acute circulatory failure related to infection [ 17 ] or myocardial infarction. [ 18 ] In this study, we evaluated microcirculatory hypoperfusion parameters available at bedside and found these “easy to use and easy to learn” tools are helpful to identify high-risk patients in acute PE.…”
Section: Discussionmentioning
confidence: 99%